ANALISIS ASUHAN KEPERAWATAN PADA PASIEN HIPERTENSI DENGAN MASALAH KEPERAWATAN NYERI AKUT YANG DIBERIKAN TINDAKAN RENDAM KAKI MENGGUNAKAN AIR HANGAT DENGAN JAHE DI WILAYAH KERJA UPTD PUSKESMAS ABIANSEMAL IV - Samalina Elizabeth Manetde (Universitas Muhammadiyah Klaten, 2023)
Hypertension is an elevation of blood pressure above normal when the blood vessels have high blood pressure (systolic blood pressure ≥140 mmHg or diastolic blood pressure ≥90 mmHg). A nursing problem that often arises in clients with hypertension is pain usually felt in the neck area up to the head. This scientific work was conducted to analyze the intervention of foot immersion techniques using warm water with ginger in Ms. S, Ms. R, and Ms. A with hypertension in dealing with acute pain nursing problems. One way to deal with acute pain is with non-pharmacological therapy. Soaking feet in warm water with ginger is one of the non - pharmacological therapies that can be applied. Often, clients and families do not know how or the benefits of foot immersion. Warm water with ginger can help alleviate acute pain problems. Implications Foot immersion using warm water with ginger can be done every 1 time a day for about 10 –20 minutes; it is done at least 3 times a week with a water temperature of 390 °C.At the meeting, the nurse gave an education and demonstration of foot immersion with warm water using ginger. The results of the technique of foot diving using hot water and ginger showed that there was a decrease in the pain scale in hypertensive clients after performing independently the administration of foot therapy with hot water and ginger; that is, from the beginning, the patient said the pain in the neck and the back part of the head like bit-kissed and repressed with a scale of pain 5 with a range (0–10), and the pain felt disappeared. After the intervention, the patient says the pain on the back and neck parts has reduced to scales 1–2 of the scale 5 with a range of (0–10). The client said she felt comfortable, calm, and relaxed.